Contributing Factors to Quail Farming Failures in Brebes and Potential Mitigation Strategies - Roni; Hasdar, Muhamad; sholihah, Amelia (Universitas Veteran Bangun Nusantara, 2024)
This study aims to identify the determinant factors leading to failure and to explore potential solutions for small-scale quail farmers in Brebes Regency. The research employs a quantitative approach, distributing questionnaires directly to 59 quail farmers in the Brebes region, including both active and inactive participants in quail farming. The questionnaire instrument is designed comprehensively to identify various factors contributing to failure in quail farming enterprises. The survey indicates that quail farmers face several major challenges, including high feed costs, low egg prices, and high quail mortality due to disease. All farmers also experience difficulties in marketing, limited capital, and threats from natural disasters. Lack of knowledge and poor farm management are additional issues, while competition with large-scale farmers makes it difficult for small-scale farmers to survive. Value-added products are considered highly profitable by all respondents. quail farmers in Brebes express a significant need for and strong support of government subsidies for feed costs, marketing assistance, training programs provided by veterinary departments, and the reinforcement of farmer organizations. Additionally, they concur that the adoption of advanced technologies, the enhancement of consumer awareness, the development of value-added products, and the expansion into new markets will contribute to greater efficiency and profitability within their operations.